2022 ICCAD CAD Contest Problem B: 3D Placement with D2D Vertical Connections - Hu, Kai-Shun; Lin, I-Jye; Huang, Yu-Hui; Chi, Hao-Yu; Wu, Yi-Hsuan; Shen, Chin-Fang Cindy (2022 IEEE/ACM International Conference On Computer Aided Design (ICCAD), 2022)
In the chiplet era, the benefits from multiple factors can be observed by splitting a large single die into multiple small dies. By having the multiple small dies with die-to-die (D2D) vertical connections, the benefits including: 1) better yield, 2) better timing/performance, and 3) better cost. How to do the netlist partitioning, cell placement in each of the small dies, and also how to determine the location of the D2D inter-connection terminals becomes a new topic.To address this chiplet era physical implementation problem, ICCAD-2022 contest encourages the research in the techniques of multi-die netlist partitioning and placement with D2D vertical connections. We provided (i) a set of benchmarks and (ii) an evaluation metric that facilitate contestants to develop, test, and evaluate their new algorithms.